100% renewable energy system in Japan: Smoothening and ancillary services. (15th August 2018) - Esteban, Miguel; Portugal-Pereira, Joana; Mclellan, Benjamin C.; Bricker, Jeremy; Farzaneh, Hooman; Djalilova, Nigora; Ishihara, Keiichi N.; Takagi, Hiroshi; Roeber, Volker
Highlights: Hourly simulation using real atmospheric data. Reliability assessment of 100% renewable energy grid. Feasibility of the system is assured provided large-scale implementation of batteries. Abstract: In the aftermath of the Paris Agreements, many countries around the globe have pledged to reduce the amount of greenhouse gas emissions being released into the atmosphere. To do so, it is important that the amount of renewable energy in the electricity grid increases. However, there are worries of the capacity of the grid to cope with intermittent energy sources. To assess the feasibility of a 100% renewable energy system in Japan, the authors conducted an hourly simulation of future electricity production based on wind, solar and tidal data. The system was shown to be stable, and the authors calculated the required capacity of electrical batteries that would be necessary to balance such a system.